Model Prototype Aplikasi Monitoring Tugas Akhir (MonTA) Mahasiswa pada STTI NIIT - Ristasari Dwi Septiana; Fajar Septian (Jurnal Informatika Universitas Pamulang, 2019)
Services for students' final tasks are very important to increase the number of graduates to be achieved by Universities. The problem faced is knowing the progress of the students' final task. The objective of this research was to build an application for monitoring the students' final task using a prototype model at STTI NIIT. The Prototype model in this research used to identify what services should be given to users. The collection of user needs is done by using the business model analysis technique to see the business processes that are occurring. Then build the prototype application model based on the requirements analysis. Function testing in this application is done by black-box testing, all of which functions can run well. Prototype this application can monitor the progress of students' final task. This application also can present consulting services for students' final task.